A Minimally Invasive Endoscopic Surgery for Infectious Spondylodiscitis of the Thoracic and Upper Lumbar Spine in Immunocompromised Patients. (26th July 2015) - Chen, Hsin-Chuan; Huang, Teng-Le; Chen, Yen-Jen; Tsou, Hsi-Kai; Lin, Wei-Ching; Hung, Chih-Hung; Tsai, Chun-Hao; Hsu, Horng-Chaung; Chen, Hsien-Te
Abstract : This study evaluates the safety and effectiveness of computed tomography- (CT-) assisted endoscopic surgery in the treatment of infectious spondylodiscitis of the thoracic and upper lumbar spine in immunocompromised patients. From October 2006 to March 2014, a total of 41 patients with infectious spondylodiscitis underwent percutaneous endoscopic surgery under local anesthesia, and 13 lesions from 13 patients on the thoracic or upper lumbar spine were selected for evaluation. A CT-guided catheter was placed before percutaneous endoscopic surgery as a guide to avoid injury to visceral organs, major vessels, and the spinal cord. All 13 patients had quick pain relief after endoscopic surgery without complications. The bacterial culture rate was 77%. Inflammatory parameters returned to normal after adequate antibiotic treatment. Postoperative radiographs showed no significant kyphotic deformity when compared with preoperative films. As of the last follow-up visit, no recurrent infections were noted. Traditional transthoracic or diaphragmatic surgery with or without posterior instrumentation is associated with high rates of morbidity and mortality, especially in elderly patients, patients with multiple comorbidities, or immunocompromised patients. Percutaneous endoscopic surgery assisted by a CT-guided catheter provides a safe and effective alternative treatment for infectious spondylodiscitis of the thoracic and upper lumbar spine.